Space cannot substitute for time in the study of the ecosystem services-human wellbeing relationship - Lumeng Liu; Jianguo Wu (Geography and Sustainability)
The relationship between ecosystem services (ES) and human well-being (HWB) is fundamental to the science and practice of sustainability. However, studies have shown conflicting results, which has been attributed to the influences of indicators, contexts, and scales. Yet, another potential factor, which has been overlooked, may be the mixed use of spatial and temporal approaches. Using twelve ES and seven well-being indicators and multiple statistical methods, we quantified and compared the spatial and temporal ES–HWB relationships for Inner Mongolia, China. The spatial and temporal relationships differed in both correlation direction and strength. Most relationships of economic and employment-related indicators with food provisioning and supporting services were temporally positive but spatially nonsignificant or negative. Some relationships of economic and employment-related indicators with water retention, sandstorm prevention, and wind erosion were temporally negative but spatially complex. However, the spatial and temporal ES–HWB relationships could also be similar in some cases. We conclude that although both the spatial and temporal approaches have merits, space generally cannot substitute for time in the study of ES–HWB relationship. Our study helps reconcile the seemingly conflicting findings in the literature, and suggests that future studies should explicitly distinguish between the spatial and temporal ES–HWB relationships.